General banking activities & customer relationship management of the general banking department of IFIC Bank Ltd. - Ahmed, Md. Faisal (BRAC University, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2017.